2021
DOI: 10.1177/1751143721996542
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of prone position in spontaneously breathing patients with COVID-19: A prospective cohort study

Abstract: We present a single centre study describing the effect of awake prone position (PP) on oxygenation and clinical outcomes in spontaneously breathing patients with novel coronavirus disease (COVID-19). Between 1st March and 30th April 2020, forty eight of 138 patients managed outside of the critical care unit with facemask oxygen, high flow nasal oxygen (HFNO) or continuous positive airway pressure (CPAP), underwent PP. Prone position was associated with significant improvement in oxygenation, lower ICU admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…After the search of the literature, 99 records were retrieved, of which only 9 studies [10][11][12][19][20][21][22][23][24] were observational comparison-group studies including both AP and supine patients, with sufficient information to calculate the overall risk of intubation, which are summarised alongside the APRONOX study in Figure 3; the funnel plot is provided as Appendix 9.…”
Section: Resultsmentioning
confidence: 99%
“…After the search of the literature, 99 records were retrieved, of which only 9 studies [10][11][12][19][20][21][22][23][24] were observational comparison-group studies including both AP and supine patients, with sufficient information to calculate the overall risk of intubation, which are summarised alongside the APRONOX study in Figure 3; the funnel plot is provided as Appendix 9.…”
Section: Resultsmentioning
confidence: 99%
“…The value of APP 39 alongside non-invasive ventilation 40 in reducing intubation is questionable, and our results uphold this. Some observational studies have reported decreased respiratory rate and excessive work of breathing amongst those awake proned resulting in a trend toward reduced intubation rate 9 , 14 , 17 , 18 . On the contrary, a prospective observational study found no benefit in reducing the risk of intubation but rather showed a trend for delay 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies support the use of APP to improve oxygenation for spontaneously breathing patients affected by respiratory failure 13 , 14 , 15 , 16 , 17 , 18 . Its effectiveness in reducing intubation rate and mortality remains unclear 19 , 20 , 21 , 22 , 23 as well as its tolerability 24 , 25 , timing and optimal duration 26 .…”
Section: Introductionmentioning
confidence: 96%
“…On admission, some patients with COVID-19 acute hypoxaemic respiratory failure (AHRF) exhibit profound hypoxaemia, combined with relatively preserved lung compliance and lung gas volume on CT chest imaging, and substantial increases in respiratory effort—tidal volumes (VT) of 15–20 ml/kg [ 1 ] and respiratory rates (RR) of 34 breaths/min [ 2 ] have been reported. As noted in [ 3 ], young, otherwise healthy adults can sustain tidal volumes of 20 ml/kg at a respiratory rate of 45 breaths/min almost indefinitely [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%